Effects of different basal media and complex additives interaction on in vitro seed germination and seedling growth of white kelampayan (Neolamarckia cadamba) - Ling, Wan Ting (Universiti Malaysia Sarawak (UNIMAS), 2015)
Neolamarckia cadamba or white kelampayan is a tropical tree species important for both industrial plantation and forest plantation in Malaysia. Yet its seed production is time-limited and its growth period of seedling is also quite long. In this study, a protocol for the effects of different basal media and complex additives interaction on in vitro seed germination and seedling growth of white kelampayan was established. The effects of different complex additives such as CW, BH, and PH at different concentrations (5, 10 and 15%) on seed germination and seedling growth were investigated. The results obtained in the study showed tbat Y2 B5 medium was the most suitable basal madia for in vitro seed germination with 45.67±1.19% of seed germination. Y2 B5 medium and 10% CW were the best combination medium for seedling growth.